Organisational development in the context of radical institutional change: the case study of Poland's Ursus - Wąsowska, Aleksandra (Business history, 2022)
The case study presented here relates to Ursus - one of the world's oldest makers of agriculture tractors. Founded in the late 19th century, and nationalised in the inter-War period, Ursus became one of the success stories of communist-era Poland. This denoted that, when the transition to a market economy took place, the enterprise came to typify state-owned 'dinosaurs'. However, once Poland had acceded to the European Union, Ursus was acquired by a family firm and began to increase its international presence rapidly once again. This paper therefore revisits the processes whereby the state firms of post-communist economies underwent organisational transformation; and sheds light on the non-linear nature of its subject's development process, unfolding in the context of radical institutional change.